Rehabilitation and In-Hospital Mortality in COVID-19 Patients. Issue 4 (22nd October 2021) - Ambrose, Anne Felicia; Kurra, Anupama; Tsirakidis, Lana; Hunt, Kate Collins; Ayers, Emmeline; Gitkind, Andrew; Yerra, Sandeep; Lo, Yungtai; Ortiz, Nicole; Jamal, Faraz; Madan, Vikram; Bartels, Matthew N; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) guidelines endorse early rehabilitation to improve outcomes in hospitalized patients, but the evidence base to support this recommendation is lacking. We examined the association between early rehabilitation and in-hospital deaths in COVID-19 patients. Method: A single-center retrospective study, involving 990 COVID-19 patients (42.4% women, mean age 67.8 years) admitted between March 1, 2020 and May 31, 2020 to a community hospital, was conducted. Association of rehabilitation during hospitalization with in-hospital mortality was examined using logistic regression analysis adjusted for demographics, length of stay, body mass index, comorbid illnesses, functional status as well as for COVID-19 presentations, treatments, and complications. Results: Over the 3-month study period, 475 (48.0%) inpatients were referred for rehabilitation. Patients who received rehabilitation were older (73.7 ± 14.0 vs 62.3 ± 17.2). There were 61 hospital deaths (12.8%) in the rehabilitation group and 165 (32.0%) in the nonrehabilitation group. Receiving rehabilitation was associated with an 89% lower in-hospital mortality (odds ratio [OR]: 0.11, 95% confidence interval [CI]: 0.06–0.19) after adjusting for multiple confounders and COVID-19 disease markers. In sensitivity analyses, the results were significant in subpopulations defined by age group, sex, race, length of hospitalization, or pulmonary presentations. Each additional rehabilitation session was associated with a 29% lower risk of in-hospital mortality (OR per session: 0.71, 95% CI: 0.64–0.79) in the fully adjusted model. Conclusion: Among hospitalized COVID-19 patients, receiving early rehabilitation was associated with lower in-hospital mortality. Our findings support implementation of rehabilitation services for COVID-19 patients in acute care settings, but further research from randomized clinical trials is needed.